THE PRINCIPAL'S MANAGEMENT MODEL IN IMPLEMENTING A DEEP LEARNING–BASED CURRICULUM TO STRENGTHEN STUDENTS' CHARACTER AT SDN 004 TELUK BAYUR - Anggunan Tunggal; Widyatmike Gede Mulawarman; Akhmad; Nurlaili; Haeruddin; Usfandi Haryaka (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study was motivated by the importance of strengthening character education at the elementary school level as a foundation for developing students' personality, morality, and social responsibility amid the challenges of globalization, the influence of digital media, and the decline of moral values. The study aimed to analyze the principal's management model in implementing a deep learning–based curriculum to strengthen students' character, including aspects of planning, organizing, implementation, supervision and evaluation, as well as supporting and inhibiting factors. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving the school principal, teachers, and parents as research informants. Data analysis was conducted through data reduction, data display, and conclusion drawing using triangulation techniques. The results of the study indicate that the principal's management model is implemented through integrated management functions. In the planning stage, the principal builds a shared understanding of deep learning–based learning and aligns curriculum documents with character development goals. In the organizing stage, the principal optimizes school resources through the establishment of a curriculum team, the distribution of teachers' roles, and the involvement of parents as educational partners. The implementation of learning is carried out through project-based activities, reflection, and collaboration that encourage the development of values such as responsibility, empathy, discipline, cooperation, and independence among students. Supervision and evaluation are conducted continuously through classroom observations, review of teaching documents, student portfolios, and feedback from parents. The success of the implementation is supported by adaptive leadership of the principal, teacher commitment, and collaboration among school members, while the obstacles include variations in teachers' readiness, limited facilities and infrastructure, limited instructional time, and the geographical conditions of the school.